Evaluation of TNF-α, IL-6, IL-10, IL-13, IL-17, aND IFN- γ Levels and Immune Responses with Cutaneous Leishmaniasis in Protection and Pathogenesis (International Journal of Environmental Sciences, 2025)
Cutaneous Leishmaniasis (CL) is one of the World's biggest and fastest-growing problems, especially in tropical areas. The World Health Organization (WHO) found that its ability to spread greatly affects disease distribution. Leishmaniasis is a disease caused by Leishmania spp. and is spread from one person to another by a vector, the sandfly. The study aimed to determine how the Leishmania parasite affects its host cell by measuring Tumor Necrosis Factor-alpha (TNF-α), interleukins (IL-6, IL-10, IL-13, IL-17), and Interferon-Gamma (IFN- γ). Materials and Methods: Two hundred and twenty-five positive cases of Cutaneous Leishmaniasis (CL) and 100 samples of control group were collected from October 2021 to March 2022. They were diagnosed in the Hospital of the Babylon Governorate, Iraq. Giemsa stain was used to diagnose infective stage of Leishmania parasite. ELISA was used to measure the level of cytokines. The results: showed that disease was present in 86 (38.22%) of the patients who lived in urban and in 139 (61.77%) of the patients who lived in rural areas, which is a significant difference (P < 0.05) between the two places of residence. The percentage of infection in males (58.22%) was more than in females (41.77%), and there were significant differences at the p<0.05 between males and females and in most age groups. However, most people admitted to hospitals with CL were males aged between 6-15 years, and the fewest were people aged under 50. Also,the results showed that men and women had different numbers of skin ulcers (p<0.01). More than 83 (58.04%) infected males had ulcers, and 41 (62.1%) had two ulcers. The chance of getting three or four ulcers was the same for both men and women. The results of serum levels were increased for TNF-α (46.53 pg/ml), IL-6 (9.94 pg/ml), IL-10 (115 pg/ml), IL-13 ( 58.08 pg/ml), IL-17 (58.14 pg/ml), and IFN-γ (38.23 pg/ml) in patients compared with the control. In conclusion: Cutaneous Leishmaniasis infection prevalence in rural areas was more than in urban areas .The increasing levels of these interleukins, TNF-α, IFN-γ indicated a disturbance of the immune system during CL infections.